2018
DOI: 10.1055/s-0044-101254
|View full text |Cite
|
Sign up to set email alerts
|

The EFSUMB Guidelines and Recommendations for the Clinical Practice of Contrast-Enhanced Ultrasound (CEUS) in Non-Hepatic Applications: Update 2017 (Short Version)

Abstract: The updated version of the EFSUMB guidelines on the application of non-hepatic contrast-enhanced ultrasound (CEUS) deals with the use of microbubble ultrasound contrast outside the liver in the many established and emerging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
229
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 246 publications
(247 citation statements)
references
References 0 publications
7
229
0
11
Order By: Relevance
“…The indications for the ultrasound examinations including contrast agent sonography (CEUS) were based on decisions of the interdisciplinary board. In accordance with earlier intensive care unit examinations and the experience with intraoperative CEUS, such examinations are supported by the new EFSUMB Guidelines and many clinical trials [8,12,13].…”
Section: Methodsmentioning
confidence: 80%
“…The indications for the ultrasound examinations including contrast agent sonography (CEUS) were based on decisions of the interdisciplinary board. In accordance with earlier intensive care unit examinations and the experience with intraoperative CEUS, such examinations are supported by the new EFSUMB Guidelines and many clinical trials [8,12,13].…”
Section: Methodsmentioning
confidence: 80%
“…However, CEUS has been reported to enable the detection of perfusion changes and extravasation of blood [5], and it is increasingly used when active abdominal bleeding is suspected, in particular in a trauma setting [6,7]. Furthermore, some reports suggested that CEUS could also represent an interesting tool in the detection of active bleeding outside the abdominal cavity [8][9][10], and the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) guidelines suggested that CEUS may detect an ongoing hemorrhage and is useful in monitoring all stages of post-procedure bleeding [11,12]. However, to our knowledge, CEUS has never been reported to enable not only the depiction of a bleeding but also the real-time demonstration of the spontaneous stop of the bleeding, as shown in this case in which CEUS played a key role in both settings.…”
Section: Discussionmentioning
confidence: 99%
“…The examiner should acquire appropriate knowledge and training in US elastography [104,105]. The operator must distinguish a good B mode US image from suboptimal images.…”
Section: Investigator Trainingmentioning
confidence: 99%